Nilai-Nilai Pendidikan Tauhid dalam Novel “Bumi Cinta” Karya Habiburrahman El Shirazy - Rostiani, Herni; Iswanto, Pepe (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2019)
Monotheism education is a teaching to know Allah SWT. To be more confident in the One God, Allah must have religious knowledge and education. Education is not only obtained at school or at home, but education can be obtained through novels. One novel that contains the values ​​of monotheism education, namely the novel